Mathematical model for designing optimized layouts of production facilities on cross-country terrain - I. M. Zuga; V. G. Khomchenko; A. N. Kuzhel; A. O. Stroyev (Омский научный вестник, 2018)
This article contains information on the obtained model of accounting the production facilities location in an area with a cross-country terrain. Two criteria are proposed for the search for an optimal interposition of technological products source facilities and receiver facilities, taking into account the height difference. A characteristic of the source facility is introduced. Examples of the way for filling tables with communication costs levels in the vertical direction and the tables with the characteristic of the source facility are given.